A novel method for endoluminal treatment of abdominal aortic aneurysms. With bare-metal Wallstent endoprostheses and endovascular coils. - Achari, A (1998)
The established therapy for symptomatic, expanding abdominal aortic aneurysms is open surgical replacement with an artificial graft. Over the last several years, there has been increasing enthusiasm for the use of endoluminal graft prostheses to exclude abdominal aortic aneurysms. However, even with rapid advances in stent graft technology, certain problems (i.e., large profile of the devices, risk of thromboembolism, poor flexibility, endoleak formation, and side-branch occlusion) have yet to be overcome. We present the case of an 85-year-old woman with multiple comorbid illnesses who underwent endoluminal repair of her expanding abdominal aortic aneurysms. We used bare-metal Wallstent endoprostheses (Schneider, Inc.; Minneapolis, Minn) in combination with endovascular coils (Cook, Inc.; Bloomington, Ind). The bare-metal Wallstent endoprostheses were used because the patient had severely narrowed iliac arteries and a large side branch originating from the aneurysm. The procedure was technically successful, and there was no significant morbidity. Follow-up angiographic evaluation at 6 months revealed no evidence of vascular enlargement; it also revealed preservation of important side branches, and spontaneous thrombosis of the aneurysms.